KONSEP MURABAHAH DALAM DIKTUM FILSAFAT EKONOMI ISLAM - Burhanuddin Al-Butary (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This article explores the concept of murabaha, in the dictum of Islamic economic philosophy. Murabahah is a form of sale and purchase in which the seller offers his merchandise by stating the price which is the sum of the acquisition price by adding a certain amount as profit. The focus of the discussion here is how a transaction is said to be murabaha? How are the instructions of the Qur'an and hadith regarding murabaha? How is the dictum of Islamic economic philosophy against murabaha? The research method used is literature, and other related references. This article provides a final review that the concept of murabahah by implementing it based on tauhid, justice and maslahah because obeying the instructions of the Qur'an and hadith is an obligation for every Muslim convert. It would be better if someone understands trading as an art as well as worship and kindness, so that it becomes motivation and passion for the perpetrators.